Cheiloscopy - A Tool For Identification in Twins - M.Sugatha; R.Jenifer Jacquiline; M.Taqiuddin Khan (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction : Lip prints are an adjuvant tool for identification in forensic medicine. The grooves onthe lips have discrete characteristics to make it different from one other. This study was conductedon 24 pairs of twins out of which 22 pairs were Monozygotic twins and 2 pairs were Dizygotictwins. Dizygotic twins are unique in all aspects while Monozygotic twins are similar phenotypicallyand genotypically. The objective of this study is to find the most common pattern in the twins , thecommonest pattern among the male and female twins and to know the variations in the pattern of lipprints among Monozygotic and Dizygotic twins.Materials and Methods: A lipstick, drawing chart and magnifying lens were the materials used torecord the imprints of the lips. A four compartment method with a clockwise direction approach wasused and the analysis was done based on Suzuki and Tsuchihashi classification.Results: The present study shows Type 1’ was the most common lip prints observed among the 24pairs of twins. This pattern was predominantly present in the right lower lip quadrant. Out of the studysubjects of 24 pairs of twins, 38 were males and 10 were females in which Type I ‘ is common in malesand type I is common in females. Among the monozygotic twins those which had < 50 % resemblancewere 14 pairs, 50% resemblance were 6 pairs, >50% resemblance were 2 pairs in which Type is thecommonest. Among the dizygotic twins, both the pairs were totally different from each other yet Typewas the common pattern.Conclusion: Based on the analysis of the lip print patterns among monozygotic twins, though similaritieswere prevailing between them , they are not identical .Whereas among dizygotic twins both the pairs oftwins are unique. Hence Lip print can be utilized as a differentiating tool for identification.